The expectations-driven US current account - Mathias Hoffmann; Michael U. Krause; Thomas Laubach (Deutsche Bundesbank, 2013)
Since 1991, survey expectations of long-run output growth for the U.S. relative to the rest of the world exhibit a pattern strikingly similar to that of the U.S. current account, and thus also to global imbalances. We show that this finding can to a large extent be rationalized in a two-region stochastic growth model simulated using expected trend growth filtered from observed productivity. In line with the intertemporal approach to the current account, a major part of the buildup of the U.S. current account deficit appears to be driven by the optimal response of households and firms to improved growth prospects.
Keywords: F32; E13; E32; D83; O40; 330; open economy; stochastic trend growth; Kalman filter; news shocks